The social life of self‐injury: exploring the communicative dimension of a very personal practice. Issue 1 (25th September 2019) - Steggals, Peter; Lawler, Steph; Graham, Ruth
Abstract: This article makes the case for a sociological focus on the communicative, relational and interactional dimensions of nonsuicidal self‐injury. While current research tends to be dominated by highly individual and intrapsychic models, it is increasingly observed that such models leave a social dimension to the practice unexplained. A burgeoning sociological literature has begun to address this paradox of the social in self‐injury; however, we argue that the role of the social must be considered beyond the issues of aetiology, social learning and social construal/construction that are typically covered in this literature. Specifically, we argue that, since the lived meanings of self‐injury directly implicate the interactional along with the intrapsychic, a more systematic focus on the role of social relations and social communication is vital. To illustrate this conceptual argument and embed it in the lived experiences of self‐injury, we draw on two case studies taken from pilot research conducted by the authors. The more thoroughly sociological approach to self‐injury that we present here offers an important compliment to the existing evidence base by reframing the absent presence of social communication contained within it, and suggesting important future directions for research.